Ungdommens tumleplads - Frøbjerg Bavnehøj og andre folkelige fest- og idrætspladser på Fyn - Wøllekær, Johnny (Forum for Idræt, 2004)
Idrætsfaciliteternes betydning for idrættens udfoldelse og udvikling. The playground of youth – Frøbjerg Bavnehøj and other popular national areas for fêtes and sports on Funen The fact that a series of areas for fêtes and sports were established where the new open air gymnastics of the time could develop was of decisive significance for the modernisation of gymnastics and sports in rural areas during the inter-war years. The majority of these sporting areas functioned as private foundations and were constructed on a voluntary basis by members of their associations. These sports areas not only provided an injection of fresh blood for gymnastics but also created space for the expansion of new branches of sport, not least for handball. Several areas of this kind for fêtes and sport were established on Funen. One of the best known was Frøbjerg Bavnehøj, which from the 1920s up until the 1960s was used for gymnastics displays. What is interesting about Frøbjerg Bavnehøj, however, is not the sports area itself but the huge hall that was erected on the site in 1930. Another example of an area for fêtes and sports on Funen is Den Gamle Have (The Old Garden) in Allerup, where the first swimming pool to be built in a rural parish was inaugurated in 1934. For young people these areas for fêtes and sports became free spaces, where they could meet under other circumstances than those that characterised their everyday lives.